Vertical Electrical Sounding-Based Delineation of Aquifer Zones in the Gowa Regency: A Case Study at Le Cendekia Islamic Boarding School - Aslim, Muhammad Arief Fitrah Istiyanto; Arsyad, Muhammad (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2025)
This study investigates the groundwater potential in the Le Cendekia Islamic Boarding School area, Gowa, using the Vertical Electrical Sounding (VES) method with a Schlumberger configuration along a 240 m survey line. The work was motivated by recurring freshwater scarcity despite previous unsuccessful drilling attempts. Field measurements of current, potential difference, and electrode spacing were processed using Microsoft Excel and inverted with Progress software to generate a 1D true resistivity model. The apparent resistivity curve shows a steady increase with depth, indicating a transition from conductive near-surface materials to more resistive formations. The inversion results delineate nine subsurface layers, with the upper 25 m dominated by alluvium and wet clay that function as aquitards due to their low permeability. Below these units lies a conductive saturated clay layer that further restricts vertical groundwater flow. A significantly more resistive layer at approximately 25–30 m is interpreted as fractured or partially consolidated sandstone, suggesting enhanced permeability and potential groundwater storage. Based on these findings, the most favorable drilling depth for preliminary groundwater exploration is recommended at 25–30 m. This study provides essential baseline information to guide groundwater development in the Le Cendekia area.